KONSEP TEOLOGI HINDU DALAM TATTWAJÑĀNA - Ida Made Windya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Religion is the system of human belief about the existence of God as the origin and return of all forms of life. The concept of divinity (theology) in Hinduism expressly states the existence of God in the form of Nirguna Brahman and Saguna Brahman. The main sources of divinity in Hinduism can be extracted from the Vedic sacred library (Sruti). Besides that divine teachings in Hinduism can be extracted from literature such as Brahma Sutra, Upanisad, Purana, Ithihasa and archipelago texts in the form of lontar. One of the lontar which describes the Hindu theology is Tattwa Jñāna. Tattwa Jñāna means knowledge about tattwa, Śivaistis pattern contains the teachings of Shiva. Verses in this lontar used Old Javanese. This book guides people who want to be free from misery and reincarnation. Sanghyang Tattwa Jñāna that must be known in advance, which is the basis of all tattwa. By recognizing Sanghyang Tattwa Jñāna, humans can understand the life and life they receive now. In TattwaJñāna, the existence of God in the form of Nirguna Brahman is mentioned as Bhaţţara Parama Śiva , while God in the form of Saguna Brahman is declared as Bhaţţara Sadā Śiva. Parama Śiva is cetana / purusa or psychiatric / highest consciousness (God), holy - pure, not yet totally influenced by cyberspace (acetana / prakerti / pradhana), calm calm, eternal eternal, not beginning, not ending; so he was given the name Nirguna Brahman. Sadā Śiva is Saguna Brahman, meaning that God has begun to take or be affected by the influence of māyā (acetana), and already has properties, functions and activities. The influence of māyā is not yet great, only in the form of use or the law of his own omnipotence which is often referred to as